2022
DOI: 10.2298/tsci200818139a
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle shape effect on the natural-convection heat transfer of hybrid nanofluid inside a U-shaped enclosure

Abstract: The effect of nanoparticle shape on the natural convection heat transfer of Cu-Al2O3/water hybrid nanofluid inside a U-shaped enclosure is presented in this paper. The governing equations are transformed into the dimensionless form using dimensionless variables. A three-node triangular finite element method is used with the Newton-Raphson method to solve the problem numerically. The streamlines and isotherms as well as the local and average Nusselt numbers are presented for the fluid flow wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…They are generally synthesized, and they mostly use metal oxides nanoparticles include Iron oxide , Aluminum oxide , Titanium oxide , Cerium oxide , Magnetite , Silicon dioxide , and Zinc oxide . These nanoparticles derive their exceptional physical-chemical properties from their smaller size, as well as their higher corner density or the sites of edge surface [53].…”
Section: B) Metallic Oxides Nanoparticlesmentioning
confidence: 99%
“…They are generally synthesized, and they mostly use metal oxides nanoparticles include Iron oxide , Aluminum oxide , Titanium oxide , Cerium oxide , Magnetite , Silicon dioxide , and Zinc oxide . These nanoparticles derive their exceptional physical-chemical properties from their smaller size, as well as their higher corner density or the sites of edge surface [53].…”
Section: B) Metallic Oxides Nanoparticlesmentioning
confidence: 99%
“…Numerous studies focusing on the impact of nanoparticle shape on thermal dissipation characteristics are available in the literature. Ali et al (2018), Asmadi et al (2022) and Madhura et al (2023), in their studies on the influence of nanoparticle shape on Nanofluid buoyant flow behavior convection of nanoliquids, discovered that the blade-shaped nanoparticle exhibits comparatively greater heat dissipation. However, Elias et al (2014) have reported that the concentric tube heat exchanger exhibited a more significant heat transfer coefficient for cylindrical nanoparticle.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that brick-shaped and small-sized nanoparticles were preferable in improving the performance of heat exchangers in the application, while the plateletshaped nanoparticles caused a decrement in performance due to high viscosity. Other studies that discussed the nanoparticle shape effects on hybrid nanofluid flow over various geometry are by Iftikhar et al [11], Dinarvand and Rostami [12], Rashid et al [13], Elnaqeeb et al [14], Iftikhar et al [15], and Asmadi et al [16].…”
Section: Introductionmentioning
confidence: 99%